A pilot study on the functional performance and acceptability of an innovative female condom (Wondaleaf®) in Malaysia - Ting RS; Wong EL; Tnay JK (Open Access Journal of Contraception, 2018)
Rachel Sing-Kiat Ting,1 Ee-Lynn Wong,2 Jessie Koh-Sing Tnay3 1School of Sociology, China University of Political Sciences and Law, Beijing, China; 2InPsych Psychological and Counselling Services, Kuala Lumpur, 3Institute of Borneo Studies, Universiti Malaysia Sarawak, Sarawak, Malaysia Background: Female condom (FC) has been available for over 30 years, but it still lacks wide acceptability. To overcome misdirection and invagination occurring in FC and to provide a wider area of protection, Wondaleaf® (WL), a new-generation adhesive FC, was recently invented. This pioneering study sought to assess the acceptability and functional performance of WL among Malaysian women. Methods: A mixed method survey was conducted in three cities of Malaysia, recruiting sexually active heterosexual women, aged 18–50, by snowball sampling method. Participants were provided with WL and initially surveyed to rate its performance in five coital usages over 2 months. After that, the participants underwent a second survey to rate their satisfaction and acceptability toward WL. Descriptive statistics on clinical failure rates were tabulated with correlational analysis performed to identify major variables contributing to WL’s functional performance and acceptability. Results: Out of the 51 enrolled participants, 31 women completed the required surveys. WL’s total clinical failure rate was 2.60% (out of 155 condom uses) with above-average ratings of functional performance. The ease of use significantly correlated with ratings of no slippage and no misdirection. The confidence in WL’s safety features significantly correlated with a sense of empowerment and protection. Conclusion: WL has a relatively low risk of clinical failures and an overall favorable acceptability among Malaysian women. However, this study also showed that its future usage largely depends on partner acceptability. It may have the potential of complementing the existing barrier toward contraceptive use. Further studies are needed to understand the global acceptability of WL. Keywords: female condom, Wondaleaf, functional performance, acceptability, Malaysian women, contraceptives methods